Livelihoods of rural elderly in Thailand: a gender perspective - Luecha, Rattiya (2018)
This thesis aims to develop a better understanding of the livelihoods of older people in rural Thailand. It asks whether their involvement in socio-economic activities in their daily life enable them to maintain their livelihoods, highlights implications for Thai government policy. Drawing on a combination of the sustainable livelihoods framework and the gender perspective, the thesis examines the multiple activities performed by older men and women and analyses the factors affecting their engagement in these activities, and their access to different types of capital. The primary data is from 2 phases of fieldwork in a village in the North of Thailand, where 22 focus groups, 69 interviews and community maps and transect walks were conducted with the elderly. Further interviews with 75 carers of the elderly were conducted during the 2nd phase of fieldwork. The thesis highlights the broad range of socio-economic activities at household and community levels in which older men and women engaged, including agricultural and non-agricultural activities for the purpose of generating income and reciprocating or supporting family members and others. These activities enable older men and women to maintain their livelihoods despite of insufficient state support. They also reveal that family support is somewhat not the main support that it is commonly assumed to be in Thai culture, and that older people often continue to support their offspring and family members financially and non-financially. Older men are more likely to provide financial support, reflecting their roles as household leaders who are responsible for financial matters, whereas older women are more likely to provide support that is based on domestic work. Older men’s perspectives of involvement in activities are much focused on income generation, which makes it difficult for them to adapt in later life, situation when they may have to stop or decrease working. Older women are more likely to engage in domestic work and assist their spouses in farming. Both older men and women are willing to engage in any community activities, which in return provide them a link to cultivate other types of capital in maintaining their livelihoods. Therefore, ageing policy should take into account gender differences, the variation in livelihoods of the elderly, and the capacity of the community.